Spatial transformations and features of their perception in Herson city on the example of the “HBK” microdistrict - Кривець, О. (Київський національний університет імені Тараса Шевченка, 2017)
Проведено ретроспективний аналіз мікрорайону ХБК, в межах тестової ділянки. Проаналізовано роль мікрорайону у формуванні планувальної структури міста, та його значення. Виявлено сучасні особливості розвитку та функціонування об’єктів в межах тестової ділянки. Охарактеризовані фактори, що впливають на поширення процесів трансформації міського простору в межах тестової ділянки. Визначено особливості просторових трансформацій в межах тестової ділянки (ревіталізація, джентрифікація, зникнення старих функцій і занепад об’єктів). Проаналізовані результати соціологічного опитування, щодо сприйняття трансформацій міського простору мешканцями ХБК.

A retrospective analysis of the KhBK microdistrict is releaved. The role of the microdistrict in the formation of the city planning structure and its significance is analyzed. The modern features of the development and functioning of objects within the test area are shown. The factors influencing the spread of spatial transformation urban space within the test area are analyzed. The features of spatial transformations within the test area (revitalization, gentrification, disappearing of old functions) are determined. The main functional purpose of the test area were the performance of industrial and residential functions. Microdistrict was a classical industrial microdistrict because it was built for the KhBK workers. But its functions are changed nowadays. Main functional purpose of the test area, for now, are recreational and services and residential functions. On the territory of the microdistrict there are objects which were revitalized: the third pavilion of Kherson Cotton Factory – become a shopping and entertainment centre «KhBK». At the same time, there are objects which were lost the “old” function and have not a new one: “Sputnik” cinema, The first and the second pavilion of Kherson Cotton Factory. One of the factors of the spatial transformation at the test area is the tendency of trade commercialization, it is inherent in all the cities of Ukraine. The results of the sociological survey on the perception transformation urban space by the inhabitants KhBK microdistrict are analyzed. However, respondents believe that in the future with the cultural function and expansion of rest zones should strengthen the housing function of the area. It should be noted that results of responses analysis are showed that in general, residents of the microdistrict have an active civic position. Also, we can state that the residents of the microdistrict are not indifferent to the spatial transformations of the district, and they are interested to know information about changes in the urban space.
Просторові трансформації та особливості їх сприйняття в місті Херсон на прикладі мікрорайону «ХБК»
Історія міст і сіл Української РСР. Херсонська область. — К. : Головна редакція УРЕ АН УРСР, 1971. С. 108 – 114. Костюк, Л.И. Херсон. Улицы помнят [Текст] // В.Ф. Ракович, И.Д. Ратнер – Путеводитель. – Симф. : Таврия, 1987. – 112 с. Мезенцев К.В., Мезенцева Н.И. Пространственные социально-экономические изменения в Киеве и агломерации / К. Мезенцев, Н. Мезенцева // Социально-экономическая география. Вестник Ассоциации российских географов-обществоведов (АРГО). – 2012. – №1. – С. 109-123. Мельник Л.В. Трансформації міського простору на прикладі тестової ділянки в м. Луцьк [Текст] / Л.В. Мельник, А.В. Орещенко, С.П. Батиченко // Вісник КНУ. Географія. – К., 2016. – Вип. 1(64). – С.53-57. Мельничук А.Л., Коковський Л.О. Відмінності сприйняття трансформації системи природокористування у міській місцевості приміської зони Києва / А. Мельничук, Л. Коковський // Київський географічний щорічник. Науковий збірник. – Вип. 9. – 2014. – С. 110-126. Официальный сайт истории города Херсона [Електронний ресурс] // URL : http://www.mycity.kherson.ua/istoriya/1978-1997-gody/1986-god.html Пітюренко Ю.І. Розвиток міст і міське розселення в Українській РСР (особливості розвитку і розміщення, типологія, територіальні системи і перспективи) : монографія [Текст] / Ю.І. Пітюренко. – К., 1972. – 187 c. Руденко Л.Г. Изменения городского пространства в Украине / Под ред. Л. Г. Руденко. — К. : 2013. — 160 с. Руденко Л.Г. Функции городов и их влияние на пространство / под ред. Л.Г. Руденко. — К. : Феникс, 2015. — 292 с. Херсон. Розроблення плану зонування території міста / Міністерство регіонального розвитку, будівництва та житлово-комунального господарства України, Державне підприємство «Український державний науково-дослідний інститут проектування міст «ДІПРОМІСТО» імені Ю.М. Білоконя. К. : 2014 р.- 91 с.
Keywords: трансформації; місто; просторові трансформації міста; функціональні зміни; сприйняття просторових трансформацій; transformation; city; spatial transformations of the city; functional changes; perception of spatial transformations